2007
DOI: 10.1302/0301-620x.89b11.18636
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations in vastus medialis obliquus and its implications in minimally-invasive total knee replacement

Abstract: The emergence of minimally-invasive total knee replacement (TKR) has led to the refinement of several surgical approaches, including the quadriceps-sparing and sub-vastus. There is some disagreement as to the precise definition of the term 'minimally-invasive', especially in regard to the preservation of vastus medialis obliquus (VMO). It is known that the termination of VMO is variable and may make these approaches difficult. We have attempted to assess the factors influencing the insertion of VMO and the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
1
10
1
Order By: Relevance
“…They reported mean ratios of 19.8% in females and 13% in males, both considerably lower than the ratios reported here. Roberts et al () also found similar sex differences in an MRI study of knees of osteoarthritis patients (mean age 41 years), and these values were also lower than in the current study. One of the problems in analysing quadriceps muscle architecture in cadaveric or symptomatic individuals, however, is the degree of atrophy, which may affect the insertion ratio.…”
Section: Discussionsupporting
confidence: 86%
“…They reported mean ratios of 19.8% in females and 13% in males, both considerably lower than the ratios reported here. Roberts et al () also found similar sex differences in an MRI study of knees of osteoarthritis patients (mean age 41 years), and these values were also lower than in the current study. One of the problems in analysing quadriceps muscle architecture in cadaveric or symptomatic individuals, however, is the degree of atrophy, which may affect the insertion ratio.…”
Section: Discussionsupporting
confidence: 86%
“…The average VMO insertion ratio (i.e., the proportion of the medial border of the patella into which the VM inserts) in non‐pathological knees has been variously reported as 44% (Roberts et al, ), 51% (Holt et al, ) and 58% (Engelina et al, ). In our study group, the initial insertion ratio was 43.53%, which is at the lower end of the scale, but in line with values of 39.5% and 43% in sedentary and athletic individuals respectively, reported by Benjafield et al ().…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus in the literature as to whether these two components are separate muscles, or whether they reflect different directional fibers of the same muscle. 2,3 On MR imaging, the normal appearance of the trilaminar quadriceps tendon manifests as low-signal tendon fibers with interdigitating fat (Fig. 1).…”
Section: Normal Anatomymentioning
confidence: 99%